Wykorzystanie wytworów dziecka w badaniach nad mediami elektronicznymi - Izdebska, Jadwiga (Wydawnictwo Naukowe UAM Poznań, 2008)
The text concerns some methodological aspects of studies on media in child life. The possibilities of using different projection techniques such as unfinished story and unfinished sentence have been presented. The analysis of the contents of child productive activity like drawing, essay, description, story, poems and letters have also been shown. These techniques determine a variety of a child ability to think, to name different situations and reactions in media. The study with above techniques allow the answer to the question concerning a child development resulting from daily contact with media.
Using productive activity of children in studies on electronic media